The potency of secondary metabolites from traditional medicine plants as anti cancer agent - Mai Efdi (Majalah Kedokteran Andalas, 2014)
The seconday metabolites from traditional medicine plants have played an important role incancer treatment. Exploration of natural active compounds from medicinal plants for cancertreatment has attracted substantial attention worldwide. Several secondary metabolites thatwere isolated fom the plants, such as vincristne, vinblastine, campthothecins, have been usedhave been used clinically for over 40 years. Numerous techniques have been developedto obtain compounds for drug discovery including isolation from plants, synthetic chemistry,screening bioassays. As part of efforts to discover phytochemicals as anticancer agent, ourgroup were isolated several compunds mainly from Annonaceae and Melliaceae family thatshowed active againts human leukemia HL-60 cells.